Determinan Niat dan Perilaku Berinfak: Sebuah Bukti Empiris dari Muslim Millenials - Herianto; Hasbi; Irnandas, Muh (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2022)
Infak as one of the Islamic financial instruments that also has a role in encouraging increased welfare and reducing social inequality. This study aims to analyze the determinants of the use of online platforms to pay infak among Indonesian millennial Muslims. This paper provides an enrichment of the determinants of intention to pay infak through a digital platform which of course is expected to be taken into consideration in policy formulation for stakeholders including philanthropic organizations. A quantitative approach with a structural equation model (SEM) was chosen in analyzing the data with the help of the SmartPLS application.3. The research sample was 76 respondents spread across several islands in Indonesia. The existing respondents are determined by the main criteria, namely Muslims aged 24-39 years who represent the Millennial generation. Data collection is done online with the help of google forms which are distributed through social media. Through this study, it was found that social presence, and ease of access to financial facilities have a positive effect on the intention to donate using a digital platform. However, when the variables of religiosity and ease of access were moderated by donating behavior,it was not found significant effect.